Human Capital Management on the Example of an Amusement Park - Romuald SZOPA; Michał KOT (Communications of International Proceedings, 2020)
The main aim of the work is to analyze the human capital management of an amusement park, and the care for human capital by the park management. The present study also draws conclusions from the opinions obtained from employees, and thanks to which the park managers will be able to improve certain processes. The research methods used of the work include critical analysis of source materials and questionnaire. The research tool used in work is a questionnaire. The study examines the activities undertaken by the amusement park related to human capital management. The survey has been conducted among seasonal park employees who work at least one season. The following hypotheses are posed in the work: internal training in an amusement park is helpful in performing daily duties at work and allows employees to develop personally, long working hours drastically affects the quality of work performed by employees, which may affect customer service, as well as an amusement park is the right place to gain experience and improve the personal customer service experience.
Keywords: Human Capital Management; Human Resources Management; Entertainment; Amusement Parks.